Kirčio atitraukimas pietų žemaičių raseiniškių tarmėje - Atkočaitytė, Daiva (Baltistica, 2000)
Shift of stress from endings in the South Žemaitian dialect of RaseiniaiThe analysis of texts and the results of statistical research indicate that the classification of the South Žemaitian Raseiniai dialects according to the type of shift of stress from endings is not precise and fixed. Evidence of shift of stress from endings may be found in the entire dialect area, only in the northern and eastern parts of the area it is more regular and in the southern part it is less regular and less thoroughgoing.The research demonstrates that the types of stress shift that are typical of the Raseiniai dialect cannot be integrated into one common rule and that shifts of stress are still in the process of taking place. Most frequently the stress is retracted from the ending with a short vowel. Shift of stress from a long circumflex ending is much less common; it is optional and is mostly a result of phrasal intonation.Shift of stress from endings in the dialect under consideration follows the same pattern. The analysis of cases of shift of stress leads one to conclude that it is due to a number of factors:1. In cases when a long unstressed ending is shortened, the word final stress becomes irrelevant and loses its distinctive function. After the stress loses some of its functions, it can be more freely retracted from the ending to any other syllable in the word.2. The number of stressed short endings is reduced due to the position of the accent in the syllable which is usually stressed in the paradigm. From short endings the stress is retracted to another syllable which may take the stress in the course of inflection.3. Stress clash avoidance is defined as the occurrence of two stresses in adjacent syllables. This speeds up the process of shift of stress. If two adjacent syllables receive the stress, the pronunciation (or articulation) of such a word or a two-word sequence usually becomes more complicated. That is why the final stress is retracted to another syllable (preceding the ending). Quite often the stressed syllable is followed by an unstressed syllable and then by a stressed again, i.e. there occurs an interval between stressed and unstressed syllables. In the case of a polysyllabic word with more than two syllables, the retracted stress falls on the syllable which is usually stressed in the word paradigm.4. Intonation also exerts an influence on stress shift. In a phrase with a falling intonation the stress on the short ending, which is at the end of the phrase (which is less meaningful there), is more likely to move to another syllable than to preserve its original position. The stress falling on the final word in the sentence is more likely to be retracted to another syllable, than that in mid-position words.Apart from these factors, the dialect stress shift may be due to highly expressive and rapid speech when the significance of a word or a phrase may be emphasized by the logical accent.Due to the reasons specified above, one may conclude that the cases of shift of stress from short endings to other syllables are on the increase and thus reflect the latest trend in this sphere of phonetics. Shift of stress from long endings is occasional and may be explained mostly by the specific intonational pattern of the phrase.
Keywords: lietuvių kalba; dialektologija; akcentologija; kirtis